2017
DOI: 10.1111/epi.13737
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay for patients undergoing invasive electrode monitoring with stereoelectroencephalography and subdural grids correlates positively with increased institutional profitability

Abstract: These data suggest that LOS may not be the best metric to assess invasive monitoring patients (i.e., SEEG or SDG), and increased LOS does not necessarily equate with lower or negative institutional financial gain. Further research into LOS should focus on specific specialties, as each may differ in terms of financial implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…First, waiting to record a spontaneous seizure can be time consuming; one study found the average length of stay to be 7 days in their invasive monitoring unit. 24 Recording of interictal activity, on the other hand, only requires a few hours of EEG monitoring. Second, the identification of the seizure onset zone is difficult, and while quantitative methods exist, some only apply to certain seizure types and their ability to predict surgical outcome has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, waiting to record a spontaneous seizure can be time consuming; one study found the average length of stay to be 7 days in their invasive monitoring unit. 24 Recording of interictal activity, on the other hand, only requires a few hours of EEG monitoring. Second, the identification of the seizure onset zone is difficult, and while quantitative methods exist, some only apply to certain seizure types and their ability to predict surgical outcome has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…There are benefits to using IED‐based networks over seizure networks. First, waiting to record a spontaneous seizure can be time consuming; one study found the average length of stay to be 7 days in their invasive monitoring unit 24 . Recording of interictal activity, on the other hand, only requires a few hours of EEG monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a longer period of implantation might pose a higher risk of infection rate (although no infections where registered in our SEEG series 7 ). As a general rule, longer admissions may have a direct negative impact in institutional profitability, however, some authors have questioned this in the particular setting of SEEG 8 . Despite this, the need to reschedule other patients for delays in beds' turnover can affect workflows and ultimately have a negative economic impact in the institution.…”
Section: Discussionmentioning
confidence: 99%